НАВЧАЛЬНИЙ ДІАЛОГ ЯК ПЕРЕДУМОВА ГОТОВНОСТІ МАЙБУТНІХ ПЕДАГОГІВ ДО ДІАЛОГІЧНОГО НАВЧАННЯ ШКОЛЯРІВ (Педагогіка вищої та середньої школи, 2007)
Dialogical approach in the professional training of teachers provides leading role of instructor and subordinate position of student into equal interaction. Training dialogue using in educational process of higher pedagogical educational establishment is a prerequisite of dialogical training of schoolchildren.